System environment propagation modeling for a Wi-Fi-Like network operating in TV white space - Elshafie, Hashim (Penerbit UTM Press, 2014)
In paper, the effect of different environment has been studied. For the next Wi-Fi generation at different frequencies 470 MHz, 790 MHz, 2.4 GHz and 5.8 GHz. since USA and UK open up unitized portions of UHF Band for unlicensed usesecondary use. The purpose and interest in using these TV white spaces (TVWS) for providing services to end user as broad-band services through Wi-Fi like connectivity. There is awareness that Wi-Fi operating in TVWS will increase coverage range, speeds, and more reliable connections than traditional Wi-Fi at 2.4 GHz or 5.8 GHz. The Log-distance path loss model simulated by Matlab in variable environments, for instant indoor urban, outdoor urban, outdoor suburban and outdoor rural. Different graphs are illustrated to view the effect of the environment and frequencies to path loss and power received within versus distances. A comparison between traditional Wi-Fi based systems working in the 2.4 GHz and 5.8 GHz and TVWS systems in 470 MHz and 790 MHz, and results show that the favorable propagation conditions characterizing the TVWS frequencies may lead to better coverage with the additional benefit of lower transmit power levels.